FINANCIAL LITERACY, LIFESTYLE, AND SELF-CONTROL MODERATION ON MILLENNIALS’ CONSUMPTIVE BEHAVIOR IN JAKARTA - Savitri, Frischa Anugerah; Handarini, Dwi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study investigates the relationship between financial literacy, lifestyle, and consumptive behaviour, with self-control as a moderating variable among the millennial sandwich generation in DKI Jakarta. From approximately 2 million millennials, an estimated 24.4% are classified as sandwich generation. Using this estimation and the Isaac and Michael table with a 5% margin of error, a sample of 350 respondents was selected through snowball sampling. A quantitative method was applied, and data were analysed using multiple linear regression (MLR) and moderated regression analysis (MRA) with SPSS version 29. The results reveal that financial literacy has a significant negative effect on consumptive behaviour, while lifestyle and self-control have significant positive effects. However, self-control does not moderate the effect of financial literacy or lifestyle on consumptive behaviour. These findings suggest that although self-control influences consumption directly, it does not alter the effects of other variables. This study emphasizes the importance of improving financial literacy as a key strategy to reduce consumptive behaviour, particularly among financially pressured groups like the sandwich generation.